Uncertainty in tacheometric measurement of convergences in tunnels - Henriques, M. J. (2006)
The variations, along time, of the distances between object points on tunnel cross-sections (convergences) may be used in real time continuous tunnel monitoring systems, as decision tools, to activate signals of alert or alarm. Electronic tacheometers, especially the motorized ones, are frequently used to measure convergences. To quantify the levels of alert and alarm one should take into account the convergence measurement uncertainty. The paper deals with modelling the uncertainty of the convergence as a function of the instrumental uncertainty parameters, using the general formula for the propagation of variances. The model is applied to a simulated tunnel, where the special case of motorized tacheometers with automatic target recognition (ATR) systems is analysed.